2021
DOI: 10.33005/ebgc.v4i1.172
|View full text |Cite
|
Sign up to set email alerts
|

The Effect Of Financial Literacy, Overconfidence, And Risk Tolerance On Investment Decision

Abstract: This study aims to test and prove whether financial literacy, overconfidence, and risk tolerance affect investment decisions. The sample in this study were 100 respondents who met the criteria (namely: living in Sidoarjo, aged 20-24 years, owning pure gold as an investment instrument, and making purchases/investments at least once in the last year). This study used multiple linear regression analysis. As a result, it is known that the variables of financial literacy and overconfiden… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
8
0
14

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(23 citation statements)
references
References 0 publications
1
8
0
14
Order By: Relevance
“…Moreover, the estimated regression result of this research (=0.514) indicates the positive and significant (t-statistics 7.139>1.96 & P-value 0.000<0.01) impact of the overconfidence on the investment decision-making process in Nepal. This result is consistent with the theory of financial behavior, and the result supports the prior findings of [30], [29], [33], [34], [36], [39], [40], [42], [44], [43], [45],…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…Moreover, the estimated regression result of this research (=0.514) indicates the positive and significant (t-statistics 7.139>1.96 & P-value 0.000<0.01) impact of the overconfidence on the investment decision-making process in Nepal. This result is consistent with the theory of financial behavior, and the result supports the prior findings of [30], [29], [33], [34], [36], [39], [40], [42], [44], [43], [45],…”
Section: Discussionsupporting
confidence: 92%
“…They revealed investment decisions are significantly influenced by herd behavior and loss aversion. In investigating the effect of overconfidence, financial literacy, and risk tolerance on investment decisions, Yulianisa and Erna Sulistyowati [36] applied multiple linear regression models and observed that overconfidence and financial literacy have a significant influence. In contrast, risk tolerance does not affect investment decisions.…”
Section: Introductionmentioning
confidence: 99%
“…The millennial investors in this study who invested in the Sharia capital market possess risk tolerance that did not have a significant impact on their investment decisions, according to previous research (Ady & Hidayat, 2019;Hidayat, 2022;Yulianis & Sulistyowati, 2021). They did not overestimate risks when making investment decisions in the Sharia capital market.…”
Section: The Effect Of Risk Tolerance On Investment Decisionsmentioning
confidence: 47%
“…Risk-averse investors, on the other hand, prefer to avoid existing risks (Pradikasari & Isbanah, 2018). Types of risk tolerance influence investment decisionmaking Budiarto & Susanti, (2017); Fridana & Asandimitra, (2020); Hikmah et al, (2020); Lathifatunnisa & Wahyuni, (2021) although in some other studies, they do not (Ady & Hidayat, 2019;Hidayat, 2022;Yulianis & Sulistyowati, 2021). Using the previous results to hypothesize, this current study formulated a hypothesis that is: H5: Risk tolerance has a positive significant effect on investment decisions.…”
Section: The Influence Of Risk Tolerance On Investment Decisionsmentioning
confidence: 87%
“…Sehingga dari upaya tersebut, membuat semakin terbukanya peluang bagi mahasiswa untuk berinvestasi. Namun, dengan meningkatnya minat dalam berinvestasi justru dimanfaatkan sejumlah pihak untuk melakukan kecurangan dengan berkedok investasi (Yulianis & Sulistyowati, 2021). Kepopuleran instrumen investasi tertentu dapat menyita perhatian anak muda untuk berinvestasi.…”
Section: Pendahuluanunclassified